The thinking machine and the educational thought - Dilina Beshiri; Edi Puka (Pensa MultiMedia, 2014)
In this paper we will present the relationship that has always occurred between people and technology, "the thinking machine". Such relationship has become so interlaced in our technologically advanced cultures, that technology is itself considered as "the destiny of our time". It is for this reason that in this paper we will try to consider some theories concerning the construction of "intelligent machines", that is, referring to the typical peculiarities of the human thought. This field's theoretical starting point is strictly physical. The possibility to artificially reproduce intelligence is related to the study of the material of the cognitive processes. The "revolution" that this prospective of study brings in all fields of knowledge is connected to the need to initiate, master and to develop the knowledge of the people-system as an indispensible precondition to whatever realization of the system-machine. On the one hand, we will analyze this idea from the point of view of information processing, defined as Artificial Intelligence, while from the other side we will analyze the cognitive processes of the people in order to obtain from the machine his/her own intelligent behaviors as well as enquire and study the cognitive processes of the people so that we can artificially identify "the internal artificial architecture" by examining the effects of the cognitive development provoked by the contact with the new technologies.